Are low self-esteem and body image dissatisfaction related with body mass index? - Unlu, Sukran; Aykut, Mualla; Borlu, Arda; Kaner, Gulsah (Progress in Nutrition, 2019)
Aim: To determine the prevalence of self-esteem and body image dissatisfaction and its association with body mass index as well as other related factors. Material/Methods: A total of 240 women in the age range of 18 to 64 with normal weight (n=80), overweight (n=80), and obesity (n=80) were involved in this cross-sectional study. Body weight and height were measured and BMI was calculated according to WHO criteria. Individuals’ self-esteem has been evaluated through Self-Esteem Inventory developed by Coopersmith. On the other hand, body image concern degrees have been evaluated by Body Image Concern Inventory. Data were statistically analyzed by chi-square, ANOVA tests, logistic regression and correlation analysis on SPSS version 16. Results: The average of self-esteem and body image concern scores is the highest in normal-weight women and the difference between the groups has been detected to be statistically significant. Self-esteem of 7.5% of the women and body image concern of 64.2% of them are low whereas self-esteem of 49.6% and body image concern of 35.8% of them are high. An inverse relationship was found among BMI, body image and self-esteem. Having low levels of socio-economic status and education, being married, having chronical diseases and obese individuals in family were determined to be associated with low self-esteem. Moreover, older age and lower socio-economic status were related with body image dissatisfaction. Conclusion: Obesity negatively affects self-esteem and body image. Overweight and obesity must be prevented not only for decreasing non-communicable diseases, but also decreasing psychosocial and physical problems in the population.